The role of endowments of higher education institutions in funding scientific research: The experience of Harvard University during the period (2012-2021) and the lessons learned - Bounihi, Meriem (Dirassat Journal Economic Issue, 2023)
This study aims to identify the role of endowments of higher education institutions in financing scientific research in general, with presenting the experience of “Harvard University” during the period (2012-2021) and the methods it used to attract endowment funds, in addition to the lessons learned from this experience. The most important results indicate that endowments represent a permanent source of funding for scientific research at “Harvard University”, as the latter relies on several methods in order to attract endowment funds, such as using the university’s website to request financial support, transparency and disclosure about the development of endowment funds and gifts it receives, providing a simple ways to facilitate the donation process through electronic payment, as well as focus on the environmental aspect and sustainability to attract the largest number of donors.